INTEGRATED RISK MANAGEMENT IN A SMALL-DIMENSIONAL LAVENDER PLANTATION IN SOUTHERN ROMANIA - Georgia BOROȘ-IACOB; Stelica CRISTEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Studying an integrated management of the risks that young entrepreneurs face in trying to establish and maintain a lavender crop has become of real interest, as the competition has become fiercer. The present article focuses on some of the results obtained from our own research, carried out in Cornatelu commune, Dambovita county, in a family holding of 7,500 sqm, in the period 20 7-20 9. The total area was divided into three equal parts, 2,500 sqm each, the first being classically (control), the second intensively, and the third ecologically managed. During the three years, all the technological stages were followed, making correlations between the applied agrotechnics, the health status of the lavender crop, the yields obtained and the ways of its valorization for each of the tested variants. Results of the research refer both to the risks arising during the vegetation period, as well as to those from the time of harvesting, processing, packaging and delivery of the products for commercialization. The average of the testing period indicated that the classic system brings yield increases of 5-9%, the quality being also superior.